Post_modellismus : Models in Art. - Krinzinger Projekte, Vienna; Bergen Kunsthall, Bergen; Christofori, Ralf; Dorscheid, Sabine; Trummer, Thomas (Wien : Krinzinger Projekte, 2005)
Belyi, Peter ; Boberg, Oliver ; Budny, Michal ; Cake, John ; Casebere, James ; Demand, Thomas ; Dörbaum, Martin ; Eldarb, Gregor ; Gaál, Miklos ; Guggisberg, Anders ; Hornig, Sabine ; Koval, Kyrill ; Lakner, Antal ; Libera, Zbigniew ; Little, Graham ; Lutz, Andres ; Mik, Aernout ; Neave, Darren ; Obrist, Hans Ulrich ; Ozawa Tsuyoshi ; Pehrson, Ola ; Raitmayr, Christoph ; Renner, Lois ; Saunders, Nina ; Schäfer, Albrecht ; Schatz, Silke ; Sherman, Cindy ; Simmons, Laurie ; Sturm, Barbara ; Suda, Yoshihiro ; Voropai, Lioudmila ; Wischnewski, Stefan ; Zwakman, Edwin
biog. p. 66-77
Duits
Engels
Post_modellismus : Models in Art, Bergen Kunsthall, Bergen, January 20 - March 2, 2006 / Krinzinger Projekte Wien, September 28 - December 17, 2005
boek